Aggregation-Dependent Changes in Susceptibility of Dictyostelium discoideum to Amphotericin B - Rossomando, Edward F. (1977)
In this study, the polyene antibiotic amphotericin B was used to induce changes in permeability and viability of the eucaryotic microorganism Dictyostelium discoideum. The results show that as the cells progress from the growth phase through stationary phase to eventual aggregation, they become increasingly resistant to both permeability changes and lysis. Plasma membranes were prepared from cells harvested at exponential growth, stationary phase, and the aggregation-competent stage, and both the neutral lipid and phospholipid content were determined. An increase in the neutral lipid and a decrease in the phospholipid were observed as the cells progressed from growth into aggregation, with the overall result that the phospholipid-sterol ratio decreased during this period. The extent of amphotericin B binding by cells from the different stages was also determined. Aggregation cells exhibited a small but significant increase in binding compared to cells from either of the other two stages. The permeability changes produced by the drug were measured as a function of temperature. Exponentially growing cells showed a marked temperature dependence for the drug effect, whereas aggregating cells did not. Rates of inactivation by the drug were also determined over a range of temperatures. With exponentially growing cells, the rate of inactivation was temperature dependent, whereas with aggregating cells it was not. Finally, drug binding for both growing and aggregating cells was temperature dependent. Thus, no binding was observed for cells of either type at 4°C. This finding suggests that the differences in the temperature dependence of the permeability changes and inactivation between the cells involve parameters other than drug binding.